2020
DOI: 10.1109/jmems.2020.3003452
|View full text |Cite
|
Sign up to set email alerts
|

SeedEZTMInterdigitated Electrodes and Multifunctional Layered Biosensor Composites (MLBCs): A Paradigm Shift in the Development ofIn VitroBioMicrosystems

Abstract: We have developed a new technology for the realization of composite biosensor systems, capable of measuring electrical and electrophysiological signals from electrogenic cells, using SeedEZ™ 3D cell culture-scaffold material. This represents a paradigm-shift for BioMEMS processing; 'Biology-Microfabrication' versus the standard 'Microfabrication-Biology' approach. An Interdigitated Electrode (IDE) developed on the 3D cell-scaffold was used to successfully monitor acute cardiomyocyte growth and controlled popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…SeedEZ is optimized for long-term growth of 3D cell cultures and complex 3D co-culture models of brain, cancer, liver, bone, connective tissues, etc. (Roberts et al, 2018;Shoemaker et al, 2018;Vukasinovic et al, 2018;Lang et al, 2019;Xiong et al, 2019;Didier et al, 2020;Jensen and Teng, 2020), and as shown herein for weeks-long growth of HepG2 cells, a hepatocellular carcinoma liver cell line (Figure 2). SeedEZ scaffolds are easy to handle.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…SeedEZ is optimized for long-term growth of 3D cell cultures and complex 3D co-culture models of brain, cancer, liver, bone, connective tissues, etc. (Roberts et al, 2018;Shoemaker et al, 2018;Vukasinovic et al, 2018;Lang et al, 2019;Xiong et al, 2019;Didier et al, 2020;Jensen and Teng, 2020), and as shown herein for weeks-long growth of HepG2 cells, a hepatocellular carcinoma liver cell line (Figure 2). SeedEZ scaffolds are easy to handle.…”
Section: Introductionsupporting
confidence: 67%
“…9,334,473), that is fixed in place at approximately mid-height of the well. SeedEZ is a 500 µm thick, transparent, hydrophilic, glass micro-fiber scaffold in which cells can be seeded in medium or hydrogel to encourage both cadherinmediated cell-cell and integrin-mediated cell-extracellular matrix (ECM) signaling (Didier et al, 2020). SeedEZ is optimized for long-term growth of 3D cell cultures and complex 3D co-culture models of brain, cancer, liver, bone, connective tissues, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Together, this work serves to demonstrate accessible approaches to the development of polymer-metal fabrications for biosensor applications, and how impedimetric data coupled with equivalent circuit analysis can result in novel multifarious data from the platform technology. The authors acknowledge that all modalities described herein are not utilized in a combinatorial fashion, however interested readers may nd them practically utilized in other collaborative works from our group 5,13,35 . COMSOL micro uidic modelling of the device with a constant 8Pa applied pressure.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to compound sensing modalities, electrical impedance 2 , electrochemical 12 and electrophysiological 13,14 measurements could increase the collection of data from a single platform chip utilizing similar readout methodologies (such as impedimetric frequency sweeps). 3D microelectrodes are a common component of next generation toolsets for cellular interrogation 4,15 .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to compound sensing modalities, electrical impedance 2 , electrochemical 12 , and electrophysiological 13 , 14 measurements utilizing similar readout methodologies (such as impedimetric frequency sweeps) increase the collection of data from a single platform chip. Three-dimensional (3D) microelectrodes are a common component of next-generation toolsets for cellular interrogation 4 , 15 .…”
Section: Introductionmentioning
confidence: 99%